Applications in Water Systems Management and Modeling (IntechOpen, 2023)
With the growth of urbanization, industrialization, and intensive agricultural practices, all superficial, inland, and marine water bodies have become the repository for large quantities of every type of substance extraneous to the natural aquatic environment. The knowledge of hydrodynamics becomes crucial in this context, as it is the driving mechanism for the movement and transport of these matters and of sediments that become collectors of these substances, in a surface water system. The best way to understand these natural processes is via examples and case studies. This book deals with practical studies of hydrodynamic processes through physical and numerical models. Researchers, together with practicing engineers, will find this book useful in making a rapid assessment of different environmental water body problems.